Novel Compounds Targeting InhA for TB Therapy - Almatar, Manaf; Makky, Essam A.; Var, Isıl; Kayar, Begum; Koksal, Fatih (Elsevier, 2018)
Tuberculosis (TB) is described as lethal disease in the world. Resistant to TB drugs is the main reason to have unfavourable outcomes in the treatment of TB. Therefore, new agents to replace existing drugs are urgently needed. Previous reports suggested that InhA inhibitors, an enoyl-ACP-reductase, might provide auspicious candidates which can be developed into novel antitubercular agents. In this review, we explain the role of InhA in the resistance of isoniazid. Furthermore, five classes of InhA inhibitors, which display novel binding modes and deliver evidence of their prosperous target engagement, have been debated.